Geochemistry of Manganese Ore Deposits of Mn-hosting Top-10 Countries with A Case Study of Egypt: A Review - Metwally Hamza; Rawan Hany (African Journal of Advanced Pure and Applied Sciences, 2023)
Manganese deposits are very important. Not only in industry but also because of its medical and life applications. Based on geochemistry, the exact Mn-forming process can be known if it’s hydrothermal, sedimentary, supergene, and so on. Globally, these Mn deposits occupy higher ranks in some countries as an economic metal. The top ten countries according to the 2022 Metal Commodity Summaries of the U.S. Geological Survey are South Africa, Gabon, Australia, China, Ukraine, Ghana, India, Côte d’Ivoire, Brazil, and Malaysia. The main four metallogenetic types of manganese ore deposits across the globe are sedimentary (or volcano-sedimentary); magmatogenic (hydrothermal or contact-metasomatic); meta-morphogenic; and weathering-related deposits. In these countries, Mn deposits occur as a result of different processes. Such as those that were formed by the hydrothermal action as manganese deposits of the Oklo Region in Gabon; Northern Guizhou in China; Nishikhal Formation in southern Odisha, India. Others were formed by supergene processes such as those of the State of Amapá in Brazil. There is an ongoing debate between investigators about the Mn-forming process in some localities of these aforementioned countries such as the Mn deposits of Kalahari in South Africa; the Mankwadzi region in southern Kibi Winnieba, Ghana. Furthermore, the Mn deposits of the Um Bogma Region, West-central Sinai, and Egypt as a case study of the present paper also differ in origin between hydrothermal and sedimentary. In the present paper, the geochemical studies of the manganese deposits of these top ten countries, done by some investigators will be surveyed and discussed.